(untitled) (BIRDEM Medical Journal, 2016)
Osteoporosis is a progressive systemic skeletal disease characterizedby reduced bone mass/density and microarchitectural deterioration of bone tissue. It is a silent disease as there are no symptoms prior to a fracture.The prevalence of osteoporosis increases markedly with age.DEXA is regarded as the gold standard technique for diagnosis of osteoporosis.Treatment for osteoporosis should include lifestyle measures including nutrition, exercise and measures to reduce falls. Adequate calcium intake and vitamin D should be provided.Effective pharmacological management strategies should always be implemented where necessary including bisphosphonate asAlendronate, Etidronate, Risedronate, andraloxifene, strontium ranelate and teriparatide. Postmenopausal osteoporosis may be treated with a bisphosphonate. If bisphosphonates are unsuitable then calcitriol may be considered.Estrogen should only be considered if there is significant risk for osteoporosis and other drugs are not suitable.New biologics agents, Denosumab and Odanacatib are approved for treatment of osteoporosis. Both target osteoclasts to rebalance bone loss and bone building.The prevention of osteoporosis should be considered in early life and should be continued by regular physical activity and a balanced diet. Birdem Med J 2015; 5(1): 30-36